DIGITAL COMMUNICATION AND ITS IMPLICATIONS FOR DEFAMATION LAW: TOWARD RESTORATIVE JUSTICE - Lubis, Rahmad; Sulaiman, Heri; Purnama, Desi; Nuranisah, Nuranisah; Mutakin, Ali (LPPM STIH Putri Maharaja, 2025)
The rise in defamation cases in the digital era has accompanied the rapid growth of social media, which enables information to spread widely and quickly. In Indonesia, regulations—notably Article 27(3) and Article 28(2) of the ITE Law—were designed to address this issue. However, their implementation has often been controversial, as they risk restricting freedom of expression and are sometimes applied repressively. This study evaluates the effectiveness of these regulations and explores the use of restorative justice as an alternative for resolving defamation cases. Employing a normative juridical approach, it analyzes various countries' laws, jurisprudence, and legal practices. The findings suggest that restorative justice mechanisms—such as mediation, apologies, and content removal—are more effective in resolving disputes than criminal approaches, which tend to escalate conflicts. Therefore, regulatory reforms, enhanced digital literacy, and collaboration among the government, social media platforms, and the community are essential to implementing restorative-based solutions. A more proportionate approach would enable Indonesia’s legal system to handle defamation cases more fairly, without undermining freedom of expression.